Why millennials and gen Z are silently leaving their jobs? Unraveling the ‘quiet quitting’ trend - Taufik, Nuryanti; Rosyadi, Agi; Aliyuddin, Muhammad (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2024)
This paper investigates the phenomenon and factors that influence quiet quitting behavior that is happening in millennial and Z generation workers. Quiet quitting is employee behavior that chooses to work moderately according to the tasks that have been given. Several previous research results found that this behavior can be anticipated by increasing job satisfaction which is influenced by empowering leadership, organizational culture, and work overload. This research was designed with a survey method and using a quantitative approach. Data collection in this study used online questionnaires distributed to workers in the age range of millennial and Z generations. The data analysis technique used in this research is Structural Equation Modelling (SEM) with AMOS software. The number of samples in this study was 600 respondents. The respondents are dominated by workers on the islands of Java and Sumatra and the rest are from other regions in Indonesia. The findings of this research highlight the negative effect of job satisfaction towards quiet quitting behavior in millennial and Z workers. Another result of this study is that there is a positive effect of empowering leadership and organizational culture on job satisfaction, while work overload have a negative effect on job satisfaction. The research results are useful information for planning strategies to retain employees and provide their best performance at work. These findings are significant to measure the factors that influence job satisfaction of millennial and generation Z employees so that they do not quiet quitting or leaving the company.